Coupled ion beam preparation device and method of anti-atomic oxygen polymer composite film

The preparation of anti-atomic oxygen polymer composite films through coupled ion beam technology solves the problem of atomic oxygen erosion in a low-Earth orbit space environment, and achieves efficient protection and long-life polymer components.

CN119736600AActive Publication Date: 2025-04-01BEIJING SCI & TECH PATENT OFFICE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411919978.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Existing polymer films are eroded by atomic oxygen in low-Earth orbit space environments, resulting in material degradation and failure. The existing protection technology has problems such as poor membrane-based adhesion and prone to cracking.

Method used

Coupled ion beam technology is used to prepare anti-atomic oxygen polymer composite films, and composite films with excellent interfacial adhesion strength and film-based synergistic deformation ability are formed through Hall ion source etching, MEVVA ion implantation, magnetic filter cathode vacuum arc deposition and high-power pulse magnetron sputtering deposition.

Benefits of technology

It significantly improves the AO erosion resistance of polymer films in complex spatial environments, extends the service life of polymer components, and solves the problems of poor film-based adhesion and prone to cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736600A_ABST
    Figure CN119736600A_ABST
Patent Text Reader

Abstract

The invention discloses a coupled ion beam preparation device and method for an anti-atomic oxygen polymer composite film. The device is composed of a winding and unwinding system, a Hall ion source etching system, an MEVVA ion implantation system, a magnetic filter cathode vacuum arc deposition system and a high-power pulse magnetron sputtering deposition system. All the systems are connected through oxygen-free copper O-shaped sealing rings; the polymer film substrate is conveyed in the equipment, and the prepared composite film layer structure is shown in figure 1; the composite film prepared on the basis of the technology has excellent interface adhesion strength and film-substrate synergistic deformation capacity, AO undercut degradation induced by protective film cracking caused by space debris collision and thermal cycling can be effectively relieved, and the service life of a polymer part is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer surface / interface modification, and more particularly to a coupled ion beam preparation device and method for an antigen-oxidation polymer composite film. Background Art

[0002] Kapton-type polyimide films have excellent thermal stability, mechanical properties, corrosion resistance, dielectric properties, radiation resistance, heat resistance and flame retardancy, and biocompatibility. At present, they have successfully served in the thermal control system and flexible solar cell array of spacecraft. However, the low-Earth orbit space environment 200-700km from the Earth's surface is harsh and complex, especially the atomic oxygen erosion effect will directly lead to the degradation and failure of polymer film materials. AO has high reactivity and intrinsic kinetic energy, which can directly break the polymer skeleton and undergo oxidation reaction, releasing volatile small molecule products. The release of these volatile products from the polymer surface will directly cause material quality loss, increased surface roughness, and macroscopic loss of gloss, discoloration and powdering, thereby greatly reducing the stability of the material.

[0003] At present, single polymer film materials with excellent performance are difficult to meet the service requirements under harsh working conditions. The development of new polymer films is very complicated and requires a lot of time and financial costs. In order to alleviate the damage problem of polymer films, researchers have constructed a protective barrier on the polymer surface through coating or vapor deposition to achieve the preparation of high-performance flexible composite films. This has been proven to be one of the effective means to improve the service stability of polymer films in space environments.

[0004] Flexible composite film preparation technologies are mainly divided into wet chemical method, thermoforming method and vapor deposition method. However, at this stage, organic protective films prepared by wet chemical method or thermoforming method may have problems such as low film density (micro defects and micro holes), easy aging and falling off in coupling environment, and pollution of optoelectronic facilities. Inorganic protective films prepared by traditional vapor deposition technology may have problems such as poor film base adhesion strength, large differences in flexibility and thermal expansion coefficient. Long-term service in space environment may cause cracking, delamination and even falling of the protective film, and ultimately lead to failure of the polymer matrix. The protection strategies currently developed by the mainstream single vapor deposition technology are mainly divided into bulk material modification method and composite film protection method.

[0005] The bulk modification method is to change the molecular structure of the polymer material by doping it with specific element groups or nanoparticles, thereby enhancing the environmental stability of the polymer matrix. Its protection mechanism is that the modified polymer material grows an inert layer in situ on the surface when exposed to extreme environments to prevent further degradation of the material. The advantage of the bulk modification method is that in the process of introducing protective groups into the polymer molecular skeleton, the chelation effect provides a strong chemical bond between the two, which overcomes some of the defects of the composite film protection method, namely stress-induced film cracking, delamination and even shedding during service. However, the bulk modification method is difficult to strike a balance between improving the environmental stability of polymer materials and maintaining their initial performance.

[0006] The composite thin film protection method is to deposit an inert thin film material on a polymer substrate based on a certain film forming technology to achieve the purpose of isolating from extreme environments. According to the differences in deposition methods and thin film materials, this technology is divided into organic thin film protection method and inorganic thin film protection method.

[0007] The organic film protection method mainly uses plasma polymerization, hot pressing or coating to prepare flexible precursor organic films on the polymer surface. Since the physical and chemical properties of organic films are similar to those of polymer substrates and the thermal expansion coefficients are close, they solve the shortcomings of inorganic films that are easy to crack and have good interface adhesion. At present, organic films still face many problems. The coupling effect of AO and ultraviolet radiation may cause the film to age and fall off. These organosilicon materials may also produce darker deposits after long-term service in this coupling environment, thereby contaminating nearby optical instruments and reflectors in solar power generation systems. In addition, due to the influence of the coating process, a large number of small holes may be introduced in the preparation process of organic films, thereby causing etching of the polymer substrate.

[0008] The inorganic thin film protection method mainly uses deposition techniques such as sol-gel, magnetron sputtering, evaporation, liquid deposition and ALD to deposit metal or non-volatile oxide films on the polymer surface. The current inorganic thin film protection method mainly faces the following three challenges. First, micro defects and micro holes will inevitably be introduced during the film deposition process. In addition, inorganic films are subject to their poor flexibility, and collisions with space debris or micrometeoroids in orbit may cause the film to crack or even penetrate. In addition, the thermal expansion coefficients of inorganic films and polymer substrates are quite different, and the coupling of AO erosion and thermal cycles can easily cause film cracking, delamination and even shedding. Because AO is extremely sensitive to surface defects of the film, these defects will become channels for AO to diffuse inward and ultimately lead to the erosion and degradation of the polymer substrate. It is difficult to achieve customized regulation of composite films through the interface construction of polymer substrates. Summary of the invention

[0009] In view of this, the present invention provides a coupled ion beam preparation device and method for an anti-proton oxygen polymer composite film. The composite film prepared based on this technology has excellent interface adhesion strength and film-base cooperative deformation ability, which can effectively alleviate the AO erosion degradation induced by the cracking of the protective film caused by space debris collision and hot and cold cycles, greatly improve the service life of polymer parts, and the prepared composite film can be used in the field of aerospace composite film materials.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] A coupled ion beam preparation device for an antigen-oxygen polymer composite film, comprising:

[0012] A vacuum chamber, a first guide chamber, a first isolation chamber, a second guide chamber, a second isolation chamber, a third guide chamber, and a third isolation chamber;

[0013] Wherein, the vacuum chamber, the first guide chamber, the first isolation chamber, the second guide chamber, the second isolation chamber, the third guide chamber and the third isolation chamber are connected in sequence through oxygen-free copper O-rings;

[0014] The vacuum chamber is provided with a first unwinding roller, a second unwinding roller, a third unwinding roller and a Hall ion source etching system, wherein the first unwinding roller and the second unwinding roller are arranged vertically; the third unwinding roller is arranged on one side below the two unwinding rollers and is higher than the first unwinding roller; the Hall ion source etching system is arranged between the second unwinding roller and the third unwinding roller;

[0015] A first guide roller and a second guide roller are arranged in the first guide chamber, the first guide roller is arranged in parallel with the third unwinding roller, and the second guide roller is arranged on one side above the first guide roller;

[0016] A fourth unwinding roller, a fifth unwinding roller and a MEVVA ion implantation system are arranged in the first isolation chamber, the fourth unwinding roller is arranged in parallel with the second guide roller, the fifth unwinding roller is arranged on one side below the fourth guide roller; the MEVVA ion implantation system is arranged between the fourth unwinding roller and the fifth unwinding roller;

[0017] A third guide roller and a fourth guide roller are arranged in the second guide chamber, the third guide roller is arranged in parallel with the fifth unwinding roller, and the fourth guide roller is arranged on one side above the third guide roller;

[0018] The second isolation chamber is provided with a sixth unwinding roller, a seventh unwinding roller and a magnetic filtration cathode vacuum arc deposition system, the sixth unwinding roller is arranged in parallel with the fourth guide roller, the seventh unwinding roller is arranged on one side below the sixth unwinding roller; the magnetic filtration cathode vacuum arc deposition system is arranged between the sixth unwinding roller and the seventh unwinding roller;

[0019] A fifth guide roller and a sixth guide roller are arranged in the third guide chamber, the fifth guide roller is arranged in parallel with the seventh unwinding roller, and the sixth guide roller is arranged on one side above the fifth guide roller;

[0020] An eighth unwinding roller, a ninth unwinding roller, a tenth unwinding roller and a high-power pulsed magnetron sputtering deposition system are arranged in the third isolation chamber. The eighth unwinding roller is arranged in parallel with the sixth guide roller, and the ninth unwinding roller is arranged on one side below the eighth unwinding roller; the tenth unwinding roller is arranged above the eighth unwinding roller and vertically arranged with the ninth unwinding roller; the high-power pulsed magnetron sputtering deposition system is arranged between the eighth unwinding roller and the ninth unwinding roller.

[0021] Preferably, the outer tops and outer bottoms of the vacuum chamber, the first isolation chamber, the second isolation chamber and the third isolation chamber are all provided with molecular pumps.

[0022] Preferably, the side wall of the vacuum chamber is provided with an observation window.

[0023] Preferably, the first isolation chamber, the second isolation chamber and the third isolation chamber are all provided with heating components and cryogenic systems; wherein the heating components and cryogenic systems in the first isolation chamber are arranged at the top, and the heating components and cryogenic systems in the second isolation chamber and the third isolation chamber are arranged at the bottom.

[0024] Another object of the present invention is to provide a method for preparing an antiproton-oxygen polymer composite film by coupled ion beam, using the above-mentioned device, and the specific steps are as follows:

[0025] S01 Unwinding

[0026] The polymer is degassed using an oven, placed in a vacuum chamber, and the unwinding process begins;

[0027] S02 Hall ion source etching system

[0028] Use Hall ion source system to perform low energy and large beam current etching on polymer substrates;

[0029] S03 MEVVA ion implantation system

[0030] The polymer matrix is ​​implanted with low-energy, high-current metal ions using the MEVVA ion implantation system. After implantation, the metal element content in the subsurface layer within 30nm is not less than 3%, and the defect density is not less than 10 16 cm -3 ;

[0031] S04 Magnetic Filter Cathodic Vacuum Arc Deposition System

[0032] The alloy buffer layer is deposited on the polymer matrix using a magnetic filtered cathode vacuum arc deposition system. The plasma is transported and regulated by a magnetic field using arc discharge. The arc spot movement rate and range are controlled by a pulsed magnetic field.

[0033] The introduction of pulsed magnetic field can greatly increase the area and movement rate of arc spot of cathode target. The plasma generated during the arc spot movement is more uniform; the effective area of ​​magnetic filtration plasma drawn by a single magnetic filtration system can be increased by 2-3 times to 350mm;

[0034] S05 High Power Pulsed Magnetron Sputtering Deposition System

[0035] The oxide barrier layer was deposited using a high-power pulsed magnetron sputtering deposition system. A high-density plasma (peak current density of 10 17 -10 19 Am -2 ); The extremely high current density promotes the collision process between electrons and target atoms, thereby significantly enhancing the target ionization rate (>70%);

[0036] S06 Rolling

[0037] After the treatment is completed, the polymer is wound up for treatment.

[0038] The present invention couples the advantages of four ion beam technologies to achieve polymer substrate surface interface structure regulation and film layer structure design to solve key technical bottlenecks such as poor film-base adhesion and easy cracking of inorganic films, thereby greatly improving the AO erosion resistance of the composite film in complex space environments.

[0039] Preferably, the degassing temperature in step S01 is 60-120°C.

[0040] Preferably, the parameters of the Hall ion source etching system in step S02 include: surface etching beam current 500-2000mA, voltage 200-500V; cleaning temperature 20-40°C, etching speed 2-10m·min -1 , the surface roughness after etching is between 100-300nm.

[0041] Preferably, the MEVVA ion implantation system parameters in step S03 include: ion energy 7-30keV, beam current intensity 3-10mA; processing speed 2-10m·min -1 The treatment dose was 5×10 15 -1×10 16 atoms cm -2 .

[0042] Preferably, the parameters of the magnetic filtration cathode vacuum arc deposition system in step S04 include: arc discharge current 80-120A, pulse current 5-30A, pulse frequency 10-100Hz; deposition thickness 10-30nm, and the deposited metal is CuNi or NiCr.

[0043] Preferably, the parameters of the high-power pulsed magnetron sputtering deposition system in step S05 include: pulse power 2-5kW, pulse width 20-50μs, modulation pulse frequency 800-1000Hz; deposition thickness is 200nm, deposition structure is equiaxed crystal structure, and deposition metal is Al2O3, Cr2O3 or ZnO.

[0044] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The prepared composite film has good AO resistance and the erosion rate can be as low as 5×10 -26 cm 3 atom -1 (Land-based atomic oxygen exposure test);

[0046] 2. The prepared composite film has high interface adhesion strength, greater than 1.5N mm -1 (45° peel test);

[0047] 3. The prepared composite film has good flexibility and the residual stress is less than -100MPa (the residual stress is calculated by the film curvature radius);

[0048] 4. The preparation temperature is less than 50°C, and the film density is high (the bulk density is calculated by the film refractive index);

[0049] 5. High preparation efficiency, low cost, and travel speed of 2-10m·min -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0051] Figure 1 A schematic diagram of the composite film structure prepared by the present invention;

[0052] Figure 2 It is a schematic diagram of a coupled ion beam preparation device of the present invention;

[0053] Figure 3The present invention is a flow chart for preparing the composite film;

[0054] in, Figure 1 middle:

[0055] 101- low stress oxide protective layer; 102- flexible alloy buffer layer; 103- Ni ion pinning mixed layer; 104- polymer matrix;

[0056] Figure 2 middle:

[0057] 201- observation window; 2021- first unwinding roller; 2022- second unwinding roller; 2023- third unwinding roller; 2024- fourth unwinding roller; 2025- fifth unwinding roller; 2026- sixth unwinding roller; 2027- seventh unwinding roller; 2028- eighth unwinding roller; 2029- ninth unwinding roller; 2030- tenth unwinding roller; 203- molecular pump; 204- Hall ion source etching system; 2051- first guide roller; 2052- second guide roller; 2053- third guide roller Roller; 2054-fourth guide roller; 2055-fifth guide roller; 2056-sixth guide roller; 206-MEVVA ion implantation system; 207-magnetic filtration cathode vacuum arc deposition system; 208-high power pulsed magnetron sputtering deposition system; 209-heating assembly; 210-deep cooling system; 211-vacuum chamber; 212-first isolation chamber; 213-second isolation chamber; 214-third isolation chamber; 215-first guide chamber; 216-second guide chamber; 217-third guide chamber. DETAILED DESCRIPTION

[0058] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] Example 1

[0060] This embodiment provides a coupled ion beam preparation device for an antigen-oxygen polymer composite film, comprising:

[0061] A vacuum chamber 211, a first guide chamber 215, a first isolation chamber 212, a second guide chamber 216, a second isolation chamber 213, a third guide chamber 217 and a third isolation chamber 214;

[0062] Among them, the vacuum chamber 211, the first guide chamber 215, the first isolation chamber 212, the second guide chamber 216, the second isolation chamber 213, the third guide chamber 217 and the third isolation chamber 214 are connected in sequence through oxygen-free copper O-rings;

[0063] A first unwinding roller 2021, a second unwinding roller 2022, a third unwinding roller 2023 and a Hall ion source etching system 204 are arranged in the vacuum chamber 211. The first unwinding roller 2021 and the second unwinding roller 2022 are arranged vertically; the third unwinding roller 2022 is arranged on one side below the second unwinding roller 2022 and is higher than the first unwinding roller 2021; the Hall ion source etching system 204 is arranged between the second unwinding roller 2022 and the third unwinding roller 2023;

[0064] A first guide roller 2051 and a second guide roller 2052 are disposed in the first guide chamber 215. The first guide roller 2051 is disposed parallel to the third unwinding roller 2023, and the second guide roller 2052 is disposed on one side above the first guide roller 2051.

[0065] The first isolation chamber 212 is provided with a fourth unwinding roller 2024, a fifth unwinding roller 2025 and a MEVVA ion implantation system 206. The fourth unwinding roller 2024 is arranged in parallel with the second guide roller 2052, and the fifth unwinding roller 2025 is arranged on one side below the fourth guide roller 2054; the MEVVA ion implantation system 206 is arranged between the fourth unwinding roller 2024 and the fifth unwinding roller 2025;

[0066] A third guide roller 2053 and a fourth guide roller 2054 are disposed in the second guide chamber 216. The third guide roller 2053 is disposed parallel to the fifth unwinding roller 2024, and the fourth guide roller 2054 is disposed on one side above the third guide roller 2023.

[0067] The second isolation chamber 213 is provided with a sixth unwinding roller 2026, a seventh unwinding roller 2027 and a magnetic filtration cathode vacuum arc deposition system 207. The sixth unwinding roller 2026 is arranged in parallel with the fourth guide roller 2054, and the seventh unwinding roller 2027 is arranged on one side below the sixth unwinding roller 2026; the magnetic filtration cathode vacuum arc deposition system 207 is arranged between the sixth unwinding roller 2026 and the seventh unwinding roller 2027;

[0068] A fifth guide roller 2055 and a sixth guide roller 2056 are disposed in the third guide chamber 217. The fifth guide roller 2055 is disposed parallel to the seventh unwinding roller 2027, and the sixth guide roller 2056 is disposed on one side above the fifth guide roller 2055.

[0069] The third isolation chamber 214 is provided with an eighth unwinding roller 2028, a ninth unwinding roller 2029, a tenth unwinding roller 2010 and a high-power pulsed magnetron sputtering deposition system 208. The eighth unwinding roller 2028 is arranged in parallel with the sixth guide roller 2056, and the ninth unwinding roller 2029 is arranged on the side below the eighth unwinding roller 2028; the tenth unwinding roller 2010 is arranged above the eighth unwinding roller 2028 and is vertically arranged with the ninth unwinding roller 2029; the high-power pulsed magnetron sputtering deposition system 208 is arranged between the eighth unwinding roller 2028 and the ninth unwinding roller 2029.

[0070] In this embodiment, molecular pumps 203 are disposed on the outer tops and outer bottoms of the vacuum chamber 211 , the first isolation chamber 212 , the second isolation chamber 213 , and the third isolation chamber 214 .

[0071] An observation window 201 is provided on the side wall of the vacuum chamber 211 .

[0072] The first isolation chamber 211, the second isolation chamber 212 and the third isolation chamber 213 are all provided with a heating component 209 and a cryogenic system 210; wherein the heating component 209 and the cryogenic system 210 in the first isolation chamber 211 are arranged at the top, and the heating component 209 and the cryogenic system 210 in the second isolation chamber 212 and the third isolation chamber 213 are arranged at the bottom.

[0073] Example 2

[0074] This embodiment provides a method for preparing an antiproton-oxygen polymer composite film by coupled ion beam, comprising the following steps:

[0075] S01 Unwinding

[0076] The polymer was degassed in an oven at 80°C, placed in a vacuum chamber, and unwinding was started;

[0077] S02 Hall ion source etching;

[0078] The polymer substrate was etched with a Hall ion source system with a low-energy, high-beam current. The surface etching beam current was 1000 mA and the voltage was 300 V. The cleaning temperature was 35 °C and the etching speed was 6 m / min. -1 , the surface roughness after etching is 150nm.

[0079] S03 MEVVA ion implantation;

[0080] Low-energy, high-current Ni ion implantation was performed on the polymer matrix using the MEVVA ion implantation system; ion energy 9 keV, beam intensity 4.5 mA; processing speed 4.5 m / min -1 The treatment dose was 6×10 15 atoms cm -2After injection, the Ni content in the subsurface layer within 30nm is 3.8%, and the defect density is about 10 16 cm -3 ;

[0081] S04 magnetic filtered cathode vacuum arc deposition;

[0082] The NiCr alloy buffer layer was deposited on the polymer matrix using a magnetic filtered cathode vacuum arc deposition system with an arc discharge current of 100A, a pulse current of 25A, a pulse frequency of 80Hz, and a processing speed of 4.0mmin -1 The deposition thickness is 25 nm. The interfacial adhesion strength between NiCr and polymer substrate is about 1.6 N mm by 45° peeling test. -1 ;

[0083] S05 high power pulsed magnetron sputtering deposition;

[0084] The Al2O3 barrier layer was deposited using a high-power pulsed magnetron sputtering deposition system with a pulse power of 4kW, a pulse width of 40μs, a modulation pulse frequency of 900Hz, and a processing speed of 4.0mmin -1 , the deposition thickness is 200nm, the film structure is an equiaxed crystal structure, the residual stress of the film is calculated by the radius of curvature method to be -85MPa, and the film stacking density is measured by ellipsometry to be 0.9788;

[0085] S06 Rolling

[0086] After the treatment, the polymer was rolled up and the AO erosion rate of the composite film was measured by land-based atomic oxygen exposure test to be 6.69×10 -26 cm 3 atom -1 .

[0087] Example 3

[0088] This embodiment provides a method for preparing an antiproton-oxygen polymer composite film by coupled ion beam, comprising the following steps:

[0089] S01 Unwinding

[0090] The polymer was degassed in an oven at 80°C, placed in a vacuum chamber, and unwinding was started;

[0091] S02 Hall ion source etching;

[0092] The polymer substrate was etched with a Hall ion source system with a low-energy, high-beam current. The surface etching beam current was 1000 mA and the voltage was 300 V. The cleaning temperature was 35 °C and the etching speed was 6 m / min. -1 , the surface roughness after etching is 150nm.

[0093] S03 MEVVA ion implantation;

[0094] Low-energy, high-current Ni ion implantation was performed on the polymer matrix using the MEVVA ion implantation system; ion energy 9 keV, beam intensity 4.5 mA; processing speed 4.5 m / min -1 The treatment dose was 10 16 atoms cm -2 After injection, the Ni content of the subsurface layer within 30 nm is 6.3%, and the defect density is about 1.7×10 16 cm -3 ;

[0095] S04 magnetic filtered cathode vacuum arc deposition;

[0096] The NiCr alloy buffer layer was deposited on the polymer matrix using a magnetic filtered cathode vacuum arc deposition system with an arc discharge current of 100A, a pulse current of 25A, a pulse frequency of 80Hz, and a processing speed of 4.0mmin -1 The deposition thickness is 25 nm. The interfacial adhesion strength between NiCr and polymer substrate is about 1.8 N mm by 45° peeling test. -1 ;

[0097] S05 high power pulsed magnetron sputtering deposition;

[0098] The Al2O3 barrier layer was deposited using a high-power pulsed magnetron sputtering deposition system with a pulse power of 4kW, a pulse width of 40μs, a modulation pulse frequency of 900Hz, and a processing speed of 4.0mmin -1 , the deposition thickness is 200nm, the film structure is an equiaxed crystal structure, the residual stress of the film is calculated by the radius of curvature method to be -67MPa, and the film stacking density is measured by ellipsometry to be 0.9779;

[0099] S06 Rolling

[0100] After the treatment, the polymer was rolled up and the AO erosion rate of the composite film was measured by land-based atomic oxygen exposure test to be 5.38×10 -26 cm 3 atom -1 .

[0101] Example 4

[0102] This embodiment provides a method for preparing an antiproton-oxygen polymer composite film by coupled ion beam, comprising the following steps:

[0103] S01 Unwinding

[0104] The polymer was degassed in an oven at 80°C, placed in a vacuum chamber, and unwinding was started;

[0105] S02 Hall ion source etching;

[0106] The polymer substrate was etched with a Hall ion source system with a low-energy, high-beam current. The surface etching beam current was 1000 mA and the voltage was 300 V. The cleaning temperature was 35 °C and the etching speed was 6 m / min. -1 , the surface roughness after etching is 150nm.

[0107] S03 MEVVA ion implantation;

[0108] Low-energy, high-current Ni ion implantation was performed on the polymer matrix using the MEVVA ion implantation system; ion energy 9 keV, beam intensity 4.5 mA; processing speed 4.5 m / min -1 The treatment dose was 6×10 15 atoms cm -2 After injection, the Ni content in the subsurface layer within 30nm is 3.8%, and the defect density is about 10 16 cm -3 ;

[0109] S04 magnetic filtered cathode vacuum arc deposition;

[0110] The NiCr alloy buffer layer was deposited on the polymer matrix using a magnetic filtered cathode vacuum arc deposition system with an arc discharge current of 100A, a pulse current of 25A, a pulse frequency of 80Hz, and a processing speed of 4.0mmin -1 The deposition thickness is 25 nm. The interfacial adhesion strength between NiCr and polymer substrate is about 1.6 N mm by 45° peeling test. -1 ;

[0111] S05 high power pulsed magnetron sputtering deposition;

[0112] The Cr2O3 barrier layer was deposited using a high-power pulsed magnetron sputtering deposition system with a pulse power of 4kW, a pulse width of 40μs, a modulation pulse frequency of 800Hz, and a processing speed of 4.0mmin -1 , the deposition thickness is 200nm, the film structure is an equiaxed crystal structure, the residual stress of the film is calculated by the radius of curvature method to be -92MPa, and the film stacking density is measured by ellipsometer to be 0.9842;

[0113] S06 Rolling

[0114] After the treatment, the polymer was rolled up and the AO erosion rate of the composite film was measured by land-based atomic oxygen exposure test to be 6.28×10 -26 cm 3atom -1 .

[0115] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0116] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A coupled ion beam preparation device for an antigen-antioxidant oxygen polymer composite film, characterized in that: include: A vacuum chamber, a first guide chamber, a first isolation chamber, a second guide chamber, a second isolation chamber, a third guide chamber, and a third isolation chamber; Wherein, the vacuum chamber, the first guide chamber, the first isolation chamber, the second guide chamber, the second isolation chamber, the third guide chamber and the third isolation chamber are connected in sequence through oxygen-free copper O-rings; The vacuum chamber is provided with a first unwinding roller, a second unwinding roller, a third unwinding roller and a Hall ion source etching system, wherein the first unwinding roller and the second unwinding roller are arranged vertically; the third unwinding roller is arranged on one side below the two unwinding rollers and is higher than the first unwinding roller; the Hall ion source etching system is arranged between the second unwinding roller and the third unwinding roller; A first guide roller and a second guide roller are arranged in the first guide chamber, the first guide roller is arranged in parallel with the third unwinding roller, and the second guide roller is arranged on one side above the first guide roller; A fourth unwinding roller, a fifth unwinding roller and a MEVVA ion implantation system are arranged in the first isolation chamber, the fourth unwinding roller is arranged in parallel with the second guide roller, the fifth unwinding roller is arranged on one side below the fourth guide roller; the MEVVA ion implantation system is arranged between the fourth unwinding roller and the fifth unwinding roller; A third guide roller and a fourth guide roller are arranged in the second guide chamber, the third guide roller is arranged in parallel with the fifth unwinding roller, and the fourth guide roller is arranged on one side above the third guide roller; The second isolation chamber is provided with a sixth unwinding roller, a seventh unwinding roller and a magnetic filtration cathode vacuum arc deposition system, the sixth unwinding roller is arranged in parallel with the fourth guide roller, the seventh unwinding roller is arranged on one side below the sixth unwinding roller; the magnetic filtration cathode vacuum arc deposition system is arranged between the sixth unwinding roller and the seventh unwinding roller; A fifth guide roller and a sixth guide roller are arranged in the third guide chamber, the fifth guide roller is arranged in parallel with the seventh unwinding roller, and the sixth guide roller is arranged on one side above the fifth guide roller; An eighth unwinding roller, a ninth unwinding roller, a tenth unwinding roller and a high-power pulsed magnetron sputtering deposition system are arranged in the third isolation chamber. The eighth unwinding roller is arranged in parallel with the sixth guide roller, and the ninth unwinding roller is arranged on one side below the eighth unwinding roller; the tenth unwinding roller is arranged above the eighth unwinding roller and vertically arranged with the ninth unwinding roller; the high-power pulsed magnetron sputtering deposition system is arranged between the eighth unwinding roller and the ninth unwinding roller.

2. The coupled ion beam preparation device for an antigen-antioxidant oxygen polymer composite film according to claim 1, characterized in that: The outer tops and outer bottoms of the vacuum chamber, the first isolation chamber, the second isolation chamber and the third isolation chamber are all provided with molecular pumps.

3. The coupled ion beam preparation device for an antigen-antioxidant oxygen polymer composite film according to claim 2, characterized in that: The side wall of the vacuum chamber is provided with an observation window.

4. The coupled ion beam preparation device for an antigen-antioxidant oxygen polymer composite film according to claim 3, characterized in that: The first isolation chamber, the second isolation chamber and the third isolation chamber are all provided with a heating component and a cryogenic system; wherein the heating component and the cryogenic system in the first isolation chamber are arranged at the top, and the heating component and the cryogenic system in the second isolation chamber and the third isolation chamber are arranged at the bottom.

5. A method for preparing an antigen-antigen oxygen polymer composite film by coupled ion beam, characterized in that: Using the device described in claim 4, the specific steps are as follows: S01 Unwinding The polymer is degassed using an oven, placed in a vacuum chamber, and the unwinding process begins; S02 Hall ion source etching system Use Hall ion source system to perform low energy and large beam current etching on polymer substrates; S03 MEVVA ion implantation system The MEVVA ion implantation system is used to implant low-energy, high-current metal ions into the polymer matrix. After implantation, the metal element content in the subsurface layer within 30nm is not less than 3%, and the defect density is not less than 10 16 cm -3 ; S04 Magnetic Filter Cathodic Vacuum Arc Deposition System The alloy buffer layer is deposited on the polymer matrix using a magnetic filtered cathode vacuum arc deposition system. The plasma is transported and regulated by a magnetic field using arc discharge. The arc spot movement rate and range are controlled by a pulsed magnetic field. S05 High Power Pulsed Magnetron Sputtering Deposition System The oxide barrier layer is deposited by a high-power pulsed magnetron sputtering deposition system, and a very high-density plasma is obtained by glow discharge, pulse power supply with a duty cycle of 1%-30% and a discharge time of 10-500μs; S06 Rolling After the treatment is completed, the polymer is wound up for treatment.

6. The method for preparing an antiproton oxygen polymer composite film by coupled ion beam according to claim 5, characterized in that: The degassing temperature in step S01 is 60-120°C.

7. The method for preparing an anti-proton oxygen polymer composite film by coupled ion beam according to claim 5, characterized in that: The parameters of the Hall ion source etching system in step S02 include: surface etching beam current 500-2000mA, voltage 200-500V; cleaning temperature 20-40°C, etching speed 2-10m·min -1 , the surface roughness after etching is between 100-300nm.

8. The method for preparing an anti-proton oxygen polymer composite film by coupled ion beam according to claim 5, characterized in that: The MEVVA ion implantation system parameters in step S03 include: ion energy 7-30keV, beam intensity 3-10mA; processing speed 2-10m·min -1 The treatment dose was 5×10 15 -1×10 16 atoms cm -2 .

9. The method for preparing an anti-proton oxygen polymer composite film by coupled ion beam according to claim 5, characterized in that: The parameters of the magnetic filtration cathode vacuum arc deposition system in step S04 include: arc discharge current 80-120A, pulse current 5-30A, pulse frequency 10-100Hz; deposition thickness 10-30nm, and deposition metal CuNi or NiCr.

10. The method for preparing an anti-proton oxygen polymer composite film by coupled ion beam according to claim 5, characterized in that: The high power pulsed magnetron sputtering deposition system parameters in step S05 include: The pulse power is 2-5kW, the pulse width is 20-50μs, and the modulation pulse frequency is 800-1000Hz; the deposition thickness is 200nm, the deposition structure is an equiaxed crystal structure, and the deposited metal is Al2O3, Cr2O3 or ZnO.

Citation Information

Patent Citations

  • Base member with bonding film, bonding method and bonded body

    CN101391496A

  • Atomic oxygen resistant polymer film material and preparation method thereof

    CN111607771A

  • Composite vacuum coating equipment and use method thereof

    CN114875358A

  • Transparent conductive film, method for depositing it, and article having it

    JP2003342734A

  • Atomic Oxygen-Resistant, Low Drag Coatings and Materials

    US20190210325A1